Development of biomaterial applications for the investigation of the influence of dynamic mechanical cues and matrix apparent stiffness on the behaviour of contractile cells - Encerrado Flores, Ana L. (2022)
Cells are continually exposed to forces from their microenvironment, i.e., the forces exerted by the extracellular matrix (ECM) and cell stiffness naturally varies within the body from hard bone to soft brain tissue. It has been observed that cell function is partly influenced by the variations in stiffness, which has been attributed to the phenomenon of cells sensing the mechanical properties of their microenvironment, and the pathways involved in this phenomenon are strongly linked to tissue healing and regeneration. Cellular functions such as proliferation, migration and differentiation have shown to be highly sensitive to changes in ECM stiffness. It is by applying force, when attached to the ECM, that most mammalian cells can sense these ECM variations in stiffness as a result of its resistance to deformation. Several mechanotransduction studies, aimed to elucidate the mechanisms behind this phenomenon, have focused on the fabrication of hydrogels with tuneable mechanical properties by the modification of the hydrogel intrinsic elastic modulus. This modification does not exclusively alter the hydrogel stiffness, however, but also other properties such as topography, architecture and chemistry of the hydrogel surfaces. This has the effect of obscuring the interpretation of results. The stiffness cells can sense can also be manipulated by altering the hydrogel thickness when constraint boundaries exist. Individual cells have been observed to sense stiff boundaries through soft synthetic hydrogels when the thickness is less than 10 µm. In contrast to these linear elastic synthetic polymers – which are the option of choice – biological tissue ECM is hard to replicate. Its mechanical complexity and fibrous inhomogeneous architecture are among factors that make its study and artificial recreation challenging. The ECM is a fibrillar non-linear elastic protein-based complex, whose elastic modulus increases in magnitude as the applied strain increases. Not many mechanotransduction studies have used protein-based hydrogels but they have demonstrated that individual cells can sense stiff materials underneath these soft non-linearly elastic hydrogels at far deeper distances (50µ to 1440µm) compared to those reported by synthetic materials (10 µm). In this study, a chitosan-gelatin cross-linked hydrogel (ChG_PA) was developed and used to design, fabricate and test a range of applications to explore the effect of mechanical cues – matrix tension, apparent stiffness, stiffness gradients and flow-induced shear stress – on cell growth, migration and differentiation, in vitro. Diverse cell lines were used to study the potentiality of these models, especially human mesenchymal stem cells (hMSC), which proved to proliferate and differentiate within hydrogels of varying uniform and graduated stiffness. All cell lines used where observed to sense the stiff materials underneath the ChG_PA hydrogels at distances ranging from 2500µm to 3000µm, depending on cell line and cell seeding density. Cell number, morphology and differentiation were seen to be strongly dependent on matrix apparent stiffness (287KPa to 3KPa), stiffness gradient (126Pa/µm to 2Pa/µm), and the combined effect of flow-induced shear (1.157 dyne/cm2) and matrix apparent stiffness (213KPa to 5KPa). Therefore, the developed artificial ECM model presented in this research project is well suited to study the role of ECM mechanical cues on the behaviour of contractile cell lines.